Human capital sustainability leadership: From personality traits to positive relational management - Di Fabio, Annamaria; Bonfiglio, Antonia; Palazzeschi, Letizia; Gori, Alessio; Svicher, Andrea (Frontiers in Psychology, 2023)
Introduction Constructing positive and supportive relationships is fundamental for healthy workers and healthy organizations and to cope with the current challenging work scenario. Organizations need to acknowledge the relevance of the relationships for workers and organizational well-being and adopt managing practices that enhance healthy relationships for sustainability and sustainable development. Methods The current research sought to investigate the associations between positive relational management (PRM) and human capital sustainability leadership (HCSL), taking into account personality traits. The big five questionnaire (BFQ), the PRM Scale (PRMS), and the HCSL Scale (HCSLS) were administered to 191 Italian workers. Results Findings displayed that PRM was able to add incremental variance over personality traits referring to HCSL. Discussion In terms of strength-based prevention perspectives for healthy organizations, PRM may be a favorable construct linked to HCSL.